Pengaruh Kompetensi, Budaya Kerja dan Kepemimpinan Terhadap Kinerja Tenaga Pendidik Di Rindam Ix Udayana - Joao Xavier Barreto Nunes; Hendrajaya .; Reny Apriliyani (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2021)
Educators have a very important role for the development of human resources quality. Therefore, the performance of educators in the Rindam IX/Udayana needs to be considered. The performance of educators is the result of work both in quality and quantity achieved by an educator in carrying out the tasks for which they are responsible. The purpose of this study was to determine the effect of competence, work culture and leadership on the performance of educators at Rindam IX Udayana. The sample used in the study was 120 respondents. Data collection was done by using a questionnaire. The data analysis technique used in this research is multiple linear regression. The results of the analysis show that competence, work culture and leadership have a positive and significant effect on the performance of educators at Rindam IX Udayana. Increasing competence, good work culture and good leadership will improve the performance of educators at Rindam IX Udayana. The competence factor has the greatest influence on the performance of educators at Rindam IX Udayana. Therefore, educators are required to master teaching materials and have the ability to provide guidance to students, to be wiseand authoritative in addressing any problems or learning process in the Rindam IX Udayana.